CONSIDERATION AND UTILIZE OF LIBRARY WEB RESOURCES BY FACULTY OF ENGINEERING COLLEGE IN EAST GODAVARI DISTRICT, ANDHRA PRADESH: A STUDY - Vinoda, B; Naick, Doraswamy (International Journal of Research -GRANTHAALAYAH, 2022)
Digital information resources are fetching more and more imperative for the academic community. The increase of technical colleges in Andhra Pradesh are quiet noteworthy and in advance of various states of India. Digital resources are measured as imperative resources of teaching, research and training. Consequently, digital resources play a important role in academic libraries as they are mostly jingle for the support of academic brilliancy and research. For these research questionnaires were distributed to the faculty members of 10 selected engineering colleges in East Godavari district of Andhra Pradesh. Accordingly, 400 questionnaire distributed amongst the faculty members of 10 engineering colleges. Out of 400, only 336 questionnaires were received back that is the overall response rate is 84%.. 27.98% of the faculties are utilize digital resources for bring up to date Knowledge. It is also found from the study that preponderance of the faculty members were satisfied with available digital resources.